Fragments of Isothermal Sections of the Gd-Ge(Si)-Ga Systems Phase Diagrams at 800 ºC - Golovataya, N. V.; Markiv, V. Ya.; Belyavina, N. M. (Київський національний університет імені Тараса Шевченка, 2013)
The Gd-rich alloys of the Gd-Ge(Si)-Ga systems have been studied by the X-ray powder diffraction. The parts of the isothermal sections of these systems (800 0C, up to 33.3 at. % Gd) have been constructed. Four ternary compounds were found to exist here, namely, 1-GdGe1.0-0.7Ga1.0-1.3 (a-ThSi2-type structure), 2-Gd11Ge9Ga1 (Ho11Ga10), 1-GdSi0.9-0.6Ga1.1-1.4 (a-ThSi2) and 2-GdSi0.9-0.6Ga0.1-0.4 (CrB). One of these compounds (2-Gd11Ge9Ga1) is in fact the Ga-stabilized solid solution on the base of the high temperature Gd11Ge10 compound. Extended solid solutions on the base of the most Gd-{Si,Ge,Ga} binary compounds was shown to form in the Gd-Ge(Si)-Ga systems.
Keywords: phase diagrams; Gd-rich alloys